Lead copper matte, zinc-copper slag and carbon-copper slag combined treatment process
Through the combined treatment process of lead-copper, zinc-copper slag and carbon-copper slag, pressurized oxidation leaching, reduction reaction and electrodeposition of copper, the problems of low copper recycling efficiency and environmental pollution in the existing technology are solved, and the problem of low copper recovery efficiency and environmental pollution in the existing technology is realized. Efficient and environmentally friendly copper recycling effect.
Patent Information
- Application Number
- CN202411576976.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art has problems such as high energy consumption, serious pollution, and economic losses when dealing with lead copper, zinc copper slag and carbon copper slag, and it is difficult to effectively recover copper and other valuable metals.
The combined treatment process of lead-copper, zinc-copper slag and carbon-copper slag is adopted to achieve efficient copper recovery and effective removal of impurities through crushing and grinding, pressurized oxidation and leaching, reduction reaction, pH adjustment and electrodeposition of copper.
This process can efficiently recover copper, reduce impurity content, improve the comprehensive recovery rate of copper, reduce environmental pollution, and reduce production costs. The process is clean, environmentally friendly and highly adaptable.
Smart Images

Figure CN119433221A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nonferrous metal hydrometallurgy, and specifically relates to a joint treatment process of lead matte, zinc copper slag and carbon copper slag. Background Art
[0002] Lead matte, zinc-copper slag, and carbon copper slag are three types of copper-rich intermediate materials produced during lead smelting, zinc smelting, and copper smelting, respectively. Lead matte is a eutectic composed of sulfides such as Cu2S, PbS, and FeS, and also contains elements such as arsenic, indium, and silver; zinc-copper slag is a mixture of metal elements such as copper and zinc, and its main component is copper, and also contains metals such as zinc, cadmium, and cobalt; carbon copper slag is mainly composed of basic copper carbonate, and also contains arsenic, gold, silver, etc. For the above-mentioned copper-rich intermediate materials, smelting companies generally sell them to outsiders, and the valuable elements contained must be discounted, causing economic losses to the companies.
[0003] Lead copper matte and zinc copper slag are both copper-containing materials with high lead and zinc content. Some companies use pyrometallurgical processes alone to process them, that is, crude copper is produced through crushing-grinding-blast furnace smelting-converter blowing, and then refined copper is produced through electrolytic refining. However, this method worsens the smelting conditions and produces a large amount of harmful lead and arsenic vapor and dust during high-temperature blowing. The crude anode copper contains too much lead, resulting in poor quality of refined copper. Some companies use a semi-wet process to first roast at low temperature, and then use sulfuric acid to leach the roasted slag to obtain copper sulfate and lead sulfate. This process has problems such as low-concentration SO2 being difficult to recycle, high corrosiveness, and high energy consumption. There are also wet processes to leach lead copper matte, but the resulting leachate has a high impurity content, the copper recovery cost in the leachate is high, and the adaptability to raw materials is poor. At the same time, there are few reports on the treatment of arsenic-containing carbon copper slag, and the arsenic-containing carbon copper slag is stored, polluting the environment; it is sold at a low price, causing certain economic losses. Summary of the invention
[0004] The invention discloses a joint treatment process of lead copper matte, zinc copper slag and carbon copper slag to solve any of the above and other potential problems in the prior art.
[0005] In order to solve the above technical problems, the technical solution of the present invention is: a joint treatment process of lead copper matte, zinc copper slag and carbon copper slag, the joint treatment process specifically comprises the following steps performed in sequence:
[0006] S1) crushing and grinding lead copper matte and zinc copper slag into particles, weighing an appropriate amount of the particles and mixing them with an acid solution, adding an appropriate amount of additive a and then performing pressure oxidation leaching to obtain a slurry;
[0007] S2) slowly adding an appropriate amount of additive b to the slurry obtained in S1) while stirring, and reacting under certain conditions to obtain a reduced liquid;
[0008] S3) adding carbon copper slag to the reduced solution obtained in S2), adjusting the pH value step by step, collecting indium in a directional manner and further adjusting the pH to remove arsenic and iron from the purified solution, filtering and separating to obtain a copper-rich neutralized solution;
[0009] S4) electroplating copper with the neutralized solution obtained in S3) to obtain grade A copper that meets national standards.
[0010] Furthermore, the particle size of the particles in S1) is not greater than 200 meshes; the zinc-copper slag accounts for 5%-50%.
[0011] The liquid-to-solid ratio of the mixture to the acid solution is 3-15 L / kg, the amount of additive a added is 0.1%-5% of the mass of the mixture, the pressure is maintained at 0.5-2 MPa, the reaction temperature is 80-180° C., the reaction time is 0.5-10 h, and the exhaust gas is discharged during the reaction, and the exhaust gas flow rate is controlled at 10-100 L / min per kilogram of the mixture.
[0012] Further, the acid-containing solution is sulfuric acid with a concentration of 50 to 300 g / L;
[0013] The additive a is one or a combination of sodium lignin sulfonate, calcium lignin sulfonate, lignin sulfonic acid, iron powder, ferrous sulfate, ferric sulfate, and iron sulfide.
[0014] Furthermore, the reaction temperature in S2) is 10-99° C., the reaction time is 0.5-10 h, the stirring speed is 50-1000 r / min, and the amount of the additive b added is 0.2-10% of the slurry mass.
[0015] Furthermore, the additive b is one or a combination of copper powder, zinc-containing ash, zinc powder, iron powder, potassium iodide, iron sulfide, hydrogen sulfide, L-ascorbic acid, and glucose.
[0016] Further, in said S3), the reaction temperature is 20-95°C, the reaction time is 0.5-5h, the stirring speed is 50-500r / min, the pH value is adjusted to 1.0-3.0, and after filtering, the pH value is further adjusted to 3.5-6.5 to co-precipitate arsenic and iron, and obtain a purified copper-rich solution. Here, copper carbonate is used to adjust the pH value, first separate and enrich indium (obtain indium-rich slag), and then remove arsenic and iron impurities in the electrolyte and carbon copper slag to obtain a copper-rich solution for subsequent copper electrowinning.
[0017] Further, the process of electrolytic copper deposition in S4) is: the current density is 150-350A / m 2The electrolyte temperature is 35-80℃, the interelectrode distance is 6-15cm, the amount of additive c added is 10-200g / t-Cu; the electrolyte is circulated internally, the total electrolyte circulation time is 1-24h, the circulation method is bottom-in and top-out, and the sulfuric acid content is 70-220g / L.
[0018] Furthermore, the copper electrowinning anode of the electrowinning copper stripping is a lead-silver alloy, a lead-tin-calcium alloy or a titanium-based lead dioxide; the cathode is a 316L stainless steel or a starting electrode; and the additive c is one or a combination of bone glue, gelatin, guar gum, field gum, casein, thiourea, polyethylene glycol, chloride ion, cobalt sulfate, abiraterone and SAS 60.
[0019] Furthermore, in the combined treatment process, the copper leaching rate in the mixture is not less than 96%, the copper leaching rate of the carbon copper slag is not less than 97.0%, and the comprehensive copper recovery rate is not less than 96%.
[0020] A grade A copper is prepared by adopting the above-mentioned combined treatment process.
[0021] The mechanism of the present invention is as follows: lead matte contains sulfides such as CuS, PbS, FeS and Ag2S. Based on the difference in oxidation thermodynamics of various sulfides, copper oxide is dissolved in the reaction solution, and lead oxide is converted into lead salt precipitation and retained in the slag, thereby achieving the separation of copper and lead in lead matte; at the same time, in order to avoid the loss of indium caused by the formation of jarosite, arsenic and iron in the solution are reduced to Fe 2+ 、As 3+ Under certain conditions, the solution is adjusted to a suitable pH value through carbon copper slag, indium is enriched by directional precipitation, and after filtration and separation, the solution pH value is adjusted again through carbon copper slag to co-precipitate arsenic and iron and obtain a purified copper-rich solution.
[0022] The beneficial effect of the present invention is that, by adopting the above technical scheme, the present invention can reduce the impurity content of iron, arsenic and the like in the leachate while efficiently leaching copper and zinc by mixing lead matte and zinc copper slag and pressurizing oxidation leaching, and at the same time, add a suitable reducing agent to reduce high-valent metal ions, effectively reduce the loss of valuable metals and facilitate the separation of impurities. Then, by neutralization with carbon copper slag, the iron and arsenic content in the neutralized liquid is further reduced, and the copper in the neutralized liquid is recovered by electrowinning. As a pH regulator, carbon copper slag not only avoids the introduction of impurities, affects the recovery of indium and the arsenic iron purification solution, but also realizes the enrichment of copper as a raw material for subsequent copper electrowinning. The process has good comprehensive recovery effect, high economic value, strong adaptability to raw materials, clean and environmentally friendly process, low equipment requirements, and is easy to achieve continuous production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The present invention is a schematic diagram of a process flow of jointly treating lead copper matte, zinc copper slag and carbon copper slag. DETAILED DESCRIPTION
[0024] The present invention is further described in detail below through the accompanying drawings and examples, but the scope of the present invention is not limited to these examples.
[0025] Example 1
[0026] like Figure 1 As shown, 200g of lead matte and zinc copper slag mixture (mass ratio 2:1) after crushing and grinding through a 200-mesh sieve is taken, and 2L of sulfuric acid solution with a concentration of 140g / L is added to slurry, 2g of sodium lignin sulfonate and 3g of ferrous sulfate are added, and the mixture is placed in a high-pressure reactor, heated to 150°C, filled with compressed air, and the pressure in the reactor is maintained at 1.15MPa for pressurized oxidation leaching. During the leaching process, the tail gas is discharged at 10L / min. After reacting for 6.0h, the slurry is placed in a normal pressure reactor, and an appropriate amount of additive copper powder is slowly added while stirring. The mixture is reacted at 80°C for 4h to obtain a reduced liquid; carbon copper slag is slowly added to the reduced liquid, the pH is controlled to about 2.0, and the reaction is maintained at a temperature of 85°C for 2h, and the solid-liquid separation is performed to obtain a feed liquid; the pH is continued to be adjusted to about 4.5, and the reaction is maintained at a temperature of 95°C for 2h, and the solid-liquid separation is performed to obtain a neutralized liquid. The neutralized liquid is decoppered by electrowinning, and the current density is 200A / m 2 The electrolyte temperature is 45°C, the inter-electrode distance is 10cm, the additives are guar gum and thiourea, the circulation volume is the entire electrolytic solution, the circulation time is 2.5h, the circulation mode is bottom-in and top-out, and the electrolysis is stopped when the copper content reaches 10g / L to obtain cathode copper and decoppered liquid, and the decoppered liquid is returned for pressurized leaching.
[0027] The copper leaching rate of the lead copper matte and zinc copper slag mixture is 98.2%; the copper leaching rate of the carbon copper slag is 99%, and the electrolytic copper removal obtains Grade A copper that meets the national standard requirements. The comprehensive copper recovery rate is 95.8%.
[0028] Example 2
[0029] Take 500g of the mixture of lead matte and zinc copper slag (mass ratio 3:1) after crushing and grinding through a 100-mesh sieve, and slurry it with 4L of 120g / L sulfuric acid solution, add 7.2g of calcium lignin sulfonate and 5g of ferric sulfate, put it into a high-pressure reactor, heat it to 150℃, fill it with compressed air, maintain the pressure in the reactor at 1.2MPa, and perform pressurized oxidation leaching. During the leaching process, exhaust gas is discharged at 20L / min. After reacting for 4.5h, the slurry is placed in a normal pressure reactor, and an appropriate amount of additive zinc-containing ash is slowly added while stirring. React at 60℃ for 2h to obtain a reduced liquid; slowly add carbon copper slag to the reduced liquid, control the pH to about 2.2, maintain the reaction at 85℃ for 2h, and separate the solid and liquid to obtain the feed liquid; continue to adjust the pH of the feed liquid to about 6.0, maintain the reaction at 95℃ for 2h, and separate the solid and liquid to obtain the neutralized liquid. The neutralized liquid feed liquid is decoppered by electrowinning, and the current density is 190A / m 2The electrolyte temperature is 46°C, the inter-electrode distance is 11cm, the additives are guar gum and abiraterone, the circulation volume is the entire electrolytic solution, the circulation time is 3.5h, the circulation mode is bottom-in and top-out, and the electrolysis is stopped when the copper content reaches 15g / L to obtain cathode copper and decoppered liquid, and the decoppered liquid is returned for pressurized leaching.
[0030] The copper leaching rate in the mixture of lead copper matte and zinc-copper slag is 96%, and the copper leaching rate in carbon copper slag is 99%. Electrolytic decoppering obtains Grade A copper that meets national standards, and the comprehensive copper recovery rate is 95.2%.
[0031] Example 3
[0032] Take 1200g of the mixture of lead matte and zinc copper slag (mass ratio 1:1) after crushing and grinding through a 50-mesh sieve, mix it with 14L of the decoppered liquid to prepare the slurry, then add concentrated sulfuric acid to a sulfuric acid concentration of 90g / L, add 17.6g of sodium lignin sulfonate and 14.2g of iron sulfide, put it into a high-pressure reactor, heat it to 135°C, fill it with compressed air, maintain the pressure in the reactor at 1.20MPa, and perform pressurized oxidation leaching. During the leaching process, the tail gas is discharged at 45L / min. After reacting for 6.0h, the slurry is placed in a normal pressure reactor, and an appropriate amount of additive iron powder is slowly added while stirring. The reaction is carried out at 80°C for 4h to obtain a reduced liquid; slowly add carbon copper slag to the reduced liquid, control the pH to about 2.0, maintain the reaction at a temperature of 85°C for 2h, and separate the solid and liquid to obtain a feed liquid; continue to adjust the pH of the feed liquid to about 5.5, maintain the reaction at a temperature of 80°C for 2h, and separate the solid and liquid to obtain a neutralized liquid. The neutralized liquid was electrolytically decoppered at a current density of 240A / m 2 The electrolyte temperature is 50℃, the interelectrode distance is 9cm, the additives are gelatin, thiourea and SAS-60, the circulation volume is all the electrolytic solution, the circulation time is 3.0h, the circulation mode is bottom-in and top-out, and the electrolysis is stopped when the copper content reaches 10g / L to obtain cathode copper and decoppered liquid, and the decoppered liquid is returned for pressurized leaching.
[0033] The copper leaching rate in the mixture of lead copper matte and zinc-copper slag is 97%, and the copper leaching rate in carbon copper slag is 98.8%. Electrolytic decoppering obtains Grade A copper that meets national standards, and the comprehensive copper recovery rate is 96%.
[0034] The above is a detailed introduction to a joint treatment process of lead copper matte, zinc copper slag and carbon copper slag provided in the embodiment of the present application. The description of the above embodiment is only used to help understand the method and its core idea of the present application; at the same time, for those of ordinary skill in the art, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
[0035] For example, certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that hardware manufacturers may use different nouns to refer to the same component. This specification and claims do not use differences in names as a way to distinguish components, but use differences in the functions of components as the criteria for distinction. As mentioned throughout the specification and claims, "including" and "comprising" are open-ended terms, so they should be interpreted as "including / including but not limited to". "Approximately" means that within an acceptable error range, those skilled in the art can solve the technical problem within a certain error range and basically achieve the technical effect. The subsequent description of the specification is a preferred embodiment of the present application, but the description is for the purpose of illustrating the general principles of the present application, and is not used to limit the scope of the present application. The scope of protection of the present application shall be determined by the definition of the attached claims.
[0036] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such a product or system. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the product or system including the elements.
[0037] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0038] The above description shows and describes several preferred embodiments of the present application, but as mentioned above, it should be understood that the present application is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the application concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not deviate from the spirit and scope of the present application, and should be within the scope of protection of the claims attached to the present application.
Claims
1. A process for the combined treatment of lead copper matte, zinc copper slag and carbon copper slag, characterized in that: The combined treatment process specifically comprises the following steps performed in sequence: S1) crushing and grinding lead copper matte and zinc copper slag into particles, weighing an appropriate amount of the particles and mixing them with an acid solution, adding an appropriate amount of additive a and then performing pressure oxidation leaching to obtain a slurry; S2) slowly adding an appropriate amount of additive b to the slurry obtained in S1) while stirring, and reacting under certain conditions to obtain a reduced liquid; S3) adding carbon copper slag to the reduced solution obtained in S2) to adjust the pH value step by step, collecting indium in a directional manner and further adjusting the pH to remove arsenic and iron from the purified solution, filtering and separating to obtain a copper-rich neutralized solution; S4) electroplating copper with the neutralized solution obtained in S3) to obtain grade A copper that meets national standards.
2. The combined treatment process according to claim 1, characterized in that: The particle size of the particles in S1) is not more than 200 mesh; The percentage of zinc-copper slag in the mixture is 5%-50%; The liquid-to-solid ratio of the mixture to the acid solution is 3-15 L / kg, the amount of additive a added is 0.1%-5% of the mass of the mixture, the pressure is maintained at 0.5-2 MPa, the reaction temperature is 80-180° C., the reaction time is 0.5-10 h, and the exhaust gas is discharged during the reaction, and the exhaust gas flow rate is controlled at 10-100 L / min per kilogram of the mixture.
3. The combined treatment process according to claim 2, characterized in that: The acid solution is sulfuric acid with a concentration of 50 to 300 g / L; The additive a is one or a combination of sodium lignin sulfonate, calcium lignin sulfonate, lignin sulfonic acid, iron powder, ferrous sulfate, ferric sulfate, and iron sulfide.
4. The combined treatment process according to claim 1, characterized in that: The reaction temperature in S2) is 10-99° C., the reaction time is 0.5-10 h, the stirring speed is 50-1000 r / min, and the amount of the additive b added is 0.2-10% of the slurry mass.
5. The combined treatment process according to claim 4, characterized in that: The additive b is one or a combination of copper powder, zinc-containing ash, zinc powder, iron powder, potassium iodide, iron sulfide, hydrogen sulfide, L-ascorbic acid, and glucose.
6. The combined treatment process according to claim 1, characterized in that: In the step S3), the reaction temperature is 20-95° C., the reaction time is 0.5-5 h, the stirring speed is 50-500 r / min, the pH value is adjusted to 1.0-3.0, and after filtering, the pH value is further adjusted to 3.5-6.5 to co-precipitate arsenic and iron, and obtain a purified copper-rich solution.
7. The combined treatment process according to claim 1, characterized in that: The process of electrolytic copper deposition in S4) is: the current density is 150-350A / m 2 The electrolyte temperature is 35-80℃, the interelectrode distance is 6-15cm, the amount of additive c added is 10-200g / t-Cu; the electrolyte is circulated internally, the total electrolyte circulation time is 1-24h, the circulation method is bottom-in and top-out, and the sulfuric acid content is 70-220g / L.
8. The combined treatment process according to claim 7, characterized in that: The copper electrowinning anode of the electrowinning copper stripping is a lead-silver alloy, a lead-tin-calcium alloy or a titanium-based lead dioxide; the cathode is 316L stainless steel or a starting electrode; the additive c is one or a combination of bone glue, gelatin, guar gum, field gum, casein, thiourea, polyethylene glycol, chloride ion, cobalt sulfate, abiraterone and SAS60.
9. The combined treatment process according to claim 7, characterized in that: In the combined treatment process, the copper leaching rate in the mixture is not less than 96%, the copper leaching rate of the carbon copper slag is not less than 97.0%, and the comprehensive copper recovery rate is not less than 95%.
10. A grade A copper, characterized in that: The grade A copper is prepared by the combined treatment process as described in any one of claims 1 to 9.